2017
DOI: 10.1017/qua.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Eolian sand and loess deposits indicate west-northwest paleowinds during the Late Pleistocene in western Wisconsin, USA

Abstract: Our study adds to the Quaternary history of eolian systems and deposits in western Wisconsin, USA, primarily within the lower Chippewa River valley. Thickness and textural patterns of loess deposits in the region indicate transport by west-northwesterly and westerly winds. Loess is thickest and coarsest on the southeastern flanks of large bedrock ridges and uplands, similar in some ways to shadow dunes. In many areas, sand was transported up and onto the western flanks of bedrock ridges as sand ramps, presumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 64 publications
3
28
0
Order By: Relevance
“…By knowing which spatial trends in loess deposits are most informative, subsequent work can then examine the spatial properties of such data, for loess with “less certain” paleoenvironmental histories. This research has done much to elucidate new loess source areas, refine our understanding of loess transport systems, and even determine the strength and directional properties of paleowinds (Stanley and Schaetzl, 2011; Luehmann et al, 2013, 2016; Schaetzl and Attig, 2013; Martignier et al, 2015; Nyland et al, 2017; Schaetzl et al, 2017; Muhs et al, 2018). In summary, much can be learned about loess deposits by studying their spatial properties.…”
Section: Methodological Approaches To the Study Of Loessmentioning
confidence: 99%
See 1 more Smart Citation
“…By knowing which spatial trends in loess deposits are most informative, subsequent work can then examine the spatial properties of such data, for loess with “less certain” paleoenvironmental histories. This research has done much to elucidate new loess source areas, refine our understanding of loess transport systems, and even determine the strength and directional properties of paleowinds (Stanley and Schaetzl, 2011; Luehmann et al, 2013, 2016; Schaetzl and Attig, 2013; Martignier et al, 2015; Nyland et al, 2017; Schaetzl et al, 2017; Muhs et al, 2018). In summary, much can be learned about loess deposits by studying their spatial properties.…”
Section: Methodological Approaches To the Study Of Loessmentioning
confidence: 99%
“…Finally, it is suggested that sampling loess within 10–20 cm of any underlying lithologic discontinuity be avoided, as there exists the potential for mixing and contamination (Schaetzl and Luehmann, 2013). Data obtained from the loess, which are presumed to represent loess that was deposited during a discrete time interval, allow the investigator to tease out patterns that can then be used to infer dust source areas or paleowind directions (Schaetzl et al, 2017). Simple characterization techniques such as isoline interpolation or graduate circle symbols are useful for data exploration and interpretation, although more advanced applications such as kriging and inverse distance weighting methods are also commonly applied to such data (Fig.…”
Section: Methodological Approaches To the Study Of Loessmentioning
confidence: 99%
“…Landscapes with discontinuous loess cover of varying thickness due to variable topography are widespread in the temperate zone, such as in the patchy loess belt of Central Europe (Bertran et al, 2016), close to last glacial inland ice margins (Schaetzl et al, in press) or in parts of the Central Asian piedmont, e.g., the Ili Basin. Polygenetic loess profiles influenced by slope processes are abundant records of the complex landscape response to climatic changes (Sprafke, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…5A; Schaetzl et al . 2018). To the east, outside the valley proper, the landscape and soils are generally wetter, having formed in loess overlying finer‐textured glacial tills (Mode & Attig 1988; Attig & Muldoon 1989; Stanley & Schaetzl 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Water tables are often deep and most of the landscape is well drained; the landscape as a whole has only a few wetlands in some of the low order stream valleys or when dammed by aeolian deposits in upland locations (Fig. 5A; Schaetzl et al 2018). To the east, outside the valley proper, the landscape and soils are generally wetter, having formed in loess overlying finertextured glacial tills (Mode & Attig 1988;Attig & Muldoon 1989;Stanley & Schaetzl 2011).…”
Section: Introductionmentioning
confidence: 99%